Biological Activities and Nutraceutical Potentials of Water Extracts from Different Parts of Cynomorium Coccineum L. (Maltese Mushroom) - Zucca Paolo; Argiolas Antonio; Nieddu Mariella; Pintus Manuela; Rosa Antonella; Sanna Fabrizio; Steri Daniela; Rescigno Antonio (Polish Journal of Food and Nutrition Sciences)
Maltese Mushroom (Cynomorium coccineum L.) is a non-photosynthetic plant that has been used in traditional medicine for many centuries. In this paper, water extracts from the whole plant, external layer and peeled plant were studied to determine the main components responsible for its biological activities, i.e., its antimicrobial, antioxidant, and anti-tyrosinase activities; its cytotoxicity against mouse melanoma B16F10 cells; and its pro-erectile activity in adult male rats. The results of electron transfer and hydrogen transfer assays showed that the antioxidant activity was mainly due to anthocyanins in the external layer, whereas the external layer and peeled plant extracts both inhibited the microbial growth of several Gram-positive strains. In contrast, the whole plant extract had the highest anti-tyrosinase activity and exhibited pro-erectile activity when administered subcutaneously. Overall, this study elucidated which parts of Maltese Mushroom are responsible for its antimicrobial, antioxidant, and anti-tyrosinase activities and thus which extracts have potential for use in nutraceutical formulations.